2010
DOI: 10.1002/jcc.21598
|View full text |Cite
|
Sign up to set email alerts
|

Parallel implementation of γ‐point pseudopotential plane‐wave DFT with exact exchange

Abstract: Semi-local functionals commonly used in density functional theory (DFT) studies of solids usually fail to reproduce localized states such as trapped holes, polarons, excitons, and solitons. This failure is ascribed to self-interaction which creates a Coulomb barrier to localization. Pragmatic approaches in which the exchange correlation functionals are augmented with small amount of exact exchange (hybrid-DFT, e.g. B3LYP and PBE0) have shown promise in rectifying this type of failure, as well as producing more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 45 publications
0
54
0
Order By: Relevance
“…Both Hartree-Fock and KLI methods have been previously implemented in all-electron and in norm-conserving pseudopotential codes by many authors, some of which we list here. 59,60,[73][74][75][76][77][78] However, the present work, as well as several other recent studies 56,[79][80][81][82] show that there continue to be non-trivial numerical challenges in the careful evaluation of the Fock exchange interaction. For the PAW method, the evaluation relies on the use of compensation pair charges (Eq.…”
Section: Discussionmentioning
confidence: 46%
“…Both Hartree-Fock and KLI methods have been previously implemented in all-electron and in norm-conserving pseudopotential codes by many authors, some of which we list here. 59,60,[73][74][75][76][77][78] However, the present work, as well as several other recent studies 56,[79][80][81][82] show that there continue to be non-trivial numerical challenges in the careful evaluation of the Fock exchange interaction. For the PAW method, the evaluation relies on the use of compensation pair charges (Eq.…”
Section: Discussionmentioning
confidence: 46%
“…In general, these algorithms use an inverse iteration (or Green's function) strategy to define a subspace over an energy range that is then subsequently diagonalized. Even though a couple of groups [310][311][312][313][314] have implemented plane-wave methods that scale from 1000-10,000's of cpus (and even larger cpus for hybrid DFT) by using 2D parallel data decompositions over the number of electrons and plane-wave expansion alongside non-trivial efforts to mask latency. Ultimately, however, the scalability of these methods is limited by the scalability of the FFT algorithm, which is limited to O (N g 1/3 ) processor (or processor groups),where N g is the number of FFT grid points.…”
Section: Large Scale Electronic Structure Calculationsmentioning
confidence: 99%
“…Experience has shown that many of the failures associated with the erroneous self-interaction term can be corrected by approaches in which the DFT exchange-correlation functionals are augmented with some fraction of exact exchange (hybrid DFT, e.g. B3LYP and PBE0) [313]. These methods have been fairly successful in many problems in molecular chemistry and solid-state physics.…”
Section: Accurate Energies Of Charged Defectsmentioning
confidence: 99%
“…5,9 The present model falls into the same category as these systems, since we have assumed non-overlapping orbitals. Even for our case where the overlap is less than 10 −7 , we see that Γ-point sampling can introduce an error due to unphysical interactions between unit cells.…”
Section: Gamma Point Approximationsmentioning
confidence: 99%